Effect of clear-felling and harvest residue removal on nitrogen and phosphorus export from drained Norway spruce mires in southern Finland - Kaila, Annu; Lauren, Ari; Sarkkola, Sakari; Koivusalo, Harri; Ukonmaanaho, Liisa; O'Driscoll, Connie; Xiao, Liwen; Asam, Zaki; Nieminen, Mika (Finnish Environment Institute, 2016)
Calibration-period/control-area approach was used to study nitrogen and phosphorus export from drained and productive Norway-spruce-dominated peatland forests following conventional stem-only and whole-tree harvesting. The study indicated high nitrogen and particulate phosphorus exports and lack of significant differences between the harvest treatments during the first 3-4 years after harvesting. The high extra nitrogen exports, increasing to a maximum level of about 10 kg ha(-1) during the third year after harvesting, were partly caused by the higher nitrate export than in previous studies. The study has a practical outcome that management of harvest residues (i.e. left on site or harvested) may not be an efficient means of mitigation of nitrogen and phosphorus exports. The high exports following harvesting underline the importance of using the best available water protection methods, such as sufficiently large wetland buffer areas, to decrease nutrient exports to watercourses from productive Norway spruce dominated peatland catchments. Peer reviewed